Efficacy of Clopidogrel for Prevention of Stroke Based on CYP2C19 Allele Status in the POINT Trial. Issue 7 (July 2020) - Meschia, James F.; Walton, Ronald L.; Farrugia, Luca P.; Ross, Owen A.; Elm, Jordan J.; Farrant, Mary; Meurer, William J.; Lindblad, Anne S.; Barsan, William; Ching, Marilou; Gentile, Nina; Ross, Michael; et al.
Abstract : Background and Purpose: Clopidogrel is an antiplatelet drug that is metabolized to its active form by the CYP2C19 enzyme. The CHANCE trial (Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events) found a significant interaction between loss-of-function allele status for the CYP2C19 gene and the effect of dual antiplatelet therapy with aspirin and clopidogrel on the rate of early recurrent stroke following acute transient ischemic attack/minor stroke. The POINT (Platelet-Oriented Inhibition in New TIA and Minor Ischemic Stroke Trial), similar in design to CHANCE but performed largely in North America and Europe, demonstrated a reduction in early recurrent stroke with dual antiplatelet therapy compared with aspirin alone. This substudy was done to evaluate a potential interaction between loss-of-function CYP2C19 alleles and outcome by treatment group in POINT. Methods: Of the 269 sites in 10 countries that enrolled patients in POINT, 134 sites participated in this substudy. DNA samples were genotyped for CYP2C19 *2, *3, and *17 alleles and classified as being carriers or noncarriers of loss-of-function alleles. Major ischemia consisted of ischemic stroke, myocardial infarction, or ischemic vascular death. Results: Nine hundred thirty-two patients provided analyzable DNA. The rates of major ischemia were 6.7% for the aspirin group versus 2.3% for the dual antiplatelet therapy group (hazard ratio, 0.33 [95% CI, 0.09–1.21]; P =0.09) among carriers of loss-of-function allele. The rates of major ischemia were 5.6% for the aspirin group versus 3.7% for the dual antiplatelet therapy group (hazard ratio, 0.65 [95% CI, 0.32–1.34]; P =0.25) among noncarriers. There was no significant interaction by genotype for major ischemia ( P =0.36) or stroke ( P =0.33). Conclusions: This substudy of POINT found no significant interaction with CYP2C19 loss-of-function carrier status and outcome by treatment group. Failure to confirm the findings from the CHANCE trial may be because the loss-of-function alleles tested are not clinically important in this context or because the 2 trials had differences in racial/ethnic composition. Additionally, differences between the 2 trials might be due to chance as our statistical power was limited to 50%. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00991029. Abstract : Supplemental Digital Content is available in the text.